The Effect of Public Infrastructure on Economic Growth in Central Maluku Regency - Latuconsina, Sah Alim; Ramly, Fahrudin; Matitaputty, Izaac Tonny (PT Mattawang Mediatama Solution, 2024)
This study aims to determine the effect of electricity infrastructure proxied with the number of customers and water infrastructure proxied with the number of customers on economic growth in Central Maluku Regency. The method used is multiple linear regression. The results showed that the number of electricity customers had a positive and significant effect on economic growth while the number of water customers had a positive but not significant effect on economic growth in Central Maluku Regency